Al-Anon newcomers: benefits of continuing attendance for six months. (3rd July 2016) - Timko, Christine; Laudet, Alexandre; Moos, Rudolf H.
ABSTRACT: Background : Al-Anon Family Groups, a 12-step mutual-help program for people concerned about another person's drinking, is the most widely used form of help by Concerned Others. Objectives : This longitudinal study examined newcomers' outcomes of attending Al-Anon. Aims were to better understand early gains from Al-Anon to inform efforts in the professional community to facilitate concerned others' attendance of and engagement in Al-Anon. Methods : We compared two groups of Al-Anon newcomers who completed surveys at baseline and 6 months later: those who discontinued attendance by the 6-month follow-up ( N = 133), and those who were still attending Al-Anon meetings ( N = 97); baseline characteristics were controlled in these comparisons. Results : Newcomers who sustained participation in Al-Anon over the first 6 months of attendance were more likely than those who discontinued participation during the same period to report gains in a variety of domains, such as learning how to handle problems due to the drinker, and increased well-being and functioning, including reduced verbal or physical abuse victimization. Newcomers to Al-Anon reported more personal gains than drinker-related gains. The most frequent drinker gain was a better relationship with the Concerned Other; attendees were more likely to report this, as well as daily, in-person contact with the drinker. Conclusion : Al-Anon participation may facilitate ongoing interaction between Concerned Others and drinkers, and help Concerned Others function and feel better. Thus, short-term participation may be beneficial. Health-care professionals should consider providing referrals to Al-Anon and monitoring early attendance.